Przekaz ustny w rodzinie wiejskiej - Żebrok, Przemysław (Studia Edukacyjne, 2021)
The study is intended to signal changes in the way of communication in a rural family, including the problem of shrinking or even disappearance of traditional oral communication. For centuries, this message has determined the transmission of broadly understood culture, including traditions and customs. At present, the spoken word, one of the typical features of peasant culture, is being forced out of family life for the sake of other forms of communication. The forum for exchanging thoughts, opinions or views has moved from the family table to the Internet, and the activity in conducting conversations is focused primarily on social media or various types of discussion forums.